Genetic Diversity of Dicranopteris and Sticherus from Rokan Hulu, Riau Based on ISSR Marker - Afni Atika Marpaung; Ratna Susandarini (Universitas Gadjah Mada, 2022)
Genetic diversity of eleven taxa consisted of Dicranoperis speciosa, D. curanii, and D. linearis with seven varieties and Sticherus truncatus with two varieties from Rokan Hulu, Riau was analyzed using ISSR markers generated from 10 primers. Nine out of ten ISSR primers produced a high level of polymorphism, with six of them showed 100% polymorphism. The genetic similarity was calculated using Jaccard's similarity coefficient, and cluster analysis using the Unweighted Pair-Group Method with Arithmetic Mean. The result showed that the genetic similarity of the eleven taxa under study ranged from 0.377 to 0.627 indicated a moderate level of genetic diversity and the clusters did not separate Dicranopteris from Sticherus.